Enhanced immune reconstitution with albuvirtide in HIV-infected immunological non-responders - Fan, Lina; Hu, Yue; Li, Rui; Ding, Jiaqi; Liu, Yuantao; Yu, Shuchang; Hu, Min; Su, Rui; Li, Yangyang; Yu, AiPing; Xie, Dong; Zhao, Qingxia; et al. (Frontiers in Cellular and Infection Microbiology, 2024)
Background. Incomplete immune recovery in people living with HIV/AIDS (PLWHA) remains an important clinical challenge with the lack of an effective strategy currently available to restore their T-cell immune response. This study aimed to evaluate the effect of Albuvirtide (ABT) on immune recovery in immunological non-responders (INRs) and attempted to explore potential mechanisms of ABT on the functionality of immune cells. Methods. In this prospective, open-label, controlled clinical study, participants with incomplete immune reconstitution (continuous ART over 5 years and CD4+T lymphocyte absolute count of <500 cells/µl or ART for 2-5 years and CD4+T cell count of <200 cells/µl with undetectable viral load) were received intensive treatment with ABT or maintained on the original ART regimen at a ratio of 1:1. Immune response and safety were examined within 24 weeks. In the cytological study, T subsets, cell apoptosis and cell autophagy were analyzed using immunofluorescence staining and flow cytometry from 25 blood specimens. Results. Both groups (n=25 each) were comparable in age, gender, and ART duration. At week 12, CD4+T cell count increased significantly in the intensive ABT group compared with control group (the change from baseline in CD4+T cell count: 45 vs. -5 cells/µL, p<0.001). After ABT discontinuation, CD4+T cell counts remained significantly higher in the intensive ABT group at week 24 (55 vs. -5 cells/µL, p=0.012). In laboratory analysis, naïve CD4+ T cell amounts were lowest among participants with unsatisfactory immune response (uIR) to ABT (p=0.001). The proportion of caspase 3+CD45RA+CD31+CD4+ T cells was significantly lower in participants with satisfactory immune response (sIR) to ABT (p<0.05). Conclusion. Significant CD4+T cell count increase suggests ABT enhances immune function in INRs which may be attributed to its antiviral properties as well as its ability to increase thymic cell output and decrease cell apoptosis.